Pelatihan Penyusunan Proposal PTK Kepada Para Guru Sekolah Dasar Di Gugus 3 Kabupaten Ende - Siprianus See; Berty Sadipun; Marselina Wali; Gregorius We'u; Adi Neneng Abdullah; Agustina Pali; Siti Arafat (Prima Abdika : Jurnal Pengabdian Masyarakat, 2021)
The responsibility of teachers as professional educators is imperative in carrying out their duties. To become professional teachers, elementary school teachers in cluster 3 of Ende sub-district feel the need to get enlightenment and scientific practice through training in the preparation of Classroom Action Research proposals, so that these teachers can create quality learning in the classroom. The method of this activity is in the form of training with stages starting from the presentation of the material by the resource team to the preparation of a Classroom Action Research proposal by the teachers. The results of this training show that on average the teachers are able to understand the concept of Classroom Action Research well with indicators that teachers can identify and determine the focus of research, determine learning strategies that are considered appropriate from relevant scientific literature, and can draft Classroom Action Research proposals. Thus this training activity has a positive impact on teacher professionalism in an effort to improve the competence of students in the classroom. For this reason, teachers are expected to continue to strive to carry out scientific activities, one of which is in the form of Classroom Action Research, so that teachers can morally continue to contribute to human resource development through the education sector.